CASE REPORT: EHRLICHIOSIS IN 4 YEARS OLD POMERANIAN DOG - Juliantari, Ni Komang Ade; Jayanti, Putu Devi; Suartha, I Nyoman (Buletin Veteriner Udayana, 2023)
The purpose of this article is to determine the successful treatment of ehrlichiosis case in a dog. Handling of ehrlichiosis in this case is using the treatment method which is the antibiotic Doxycycline. The dog is a 4-year-old Pomeranian dog, named Husky, female, and with a body weight of 2.7 kg. Initially, Husky were taken to the Estimo Pet House & Clinic with complaints of being bitten by a large dog. The presence of torn wounds on the ventral abdomen and medial right thigh. However, when treated there is a suspicion of blood parasites. The results of the physical examination in general are weakness, pale eye and mouth mucosa, CRT >2 seconds, and fever. Observations found ticks Rhipicephalus sanguineus. The results of hematological examination show anemia, leukopenia, neutropenia, lymphopenia, and thrombocytopenia. The results of the blood smear showed the presence of Ehrlichia sp. The results of the snap test showed a positive result of E. canis. Based on the anamnesis, clinical signs, all of the examinations, then the dog is diagnosed ehrlichiosis with a prognosis of fausta. The treatment that given to this dog is by restoring postoperative conditions by giving 0.9% sodium chloride infusion, carprofen (Rymadyl®) dose 4 mg/kg PO, nexgard (NexGard® S) 1 chewable tablet, cefotaxime (Cefotaxime®) dose 10 mg/kg IV, hematodin (Hematodin®) 1 ml IV.  After 3 days of hospitalization, suture wounds are given Bioplacenton ointment (Bioplacenton®). After the 5th day the dog is already allowed to go home with the condition has improved. Dog were given Doxycycline (Doxilin-DT) dose 5 mg/kg BB PO for 14 days, Carprofen (Rymadyl®) dose 4 mg/kg PO for 7 days, and Sangobion (Sangobion®) 1 capsule PO for 14 days. Monitoring of the dog condition with communication to the owner that for 1 week of treatment the dog shows good activity, good appetite, as well as the absence of tick infestation. It is necessary to do a hematology test after treatment for two weeks to be able to confirm that the infection has completely disappeared and if the results still direct to blood parasites, Doxycycline can be given again because actually the treatment is recommended for 28 days.